2008
DOI: 10.1016/j.vetpar.2007.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Natural postnatal Neospora caninum infection in cattle can persist and lead to endogenous transplacental infection

Abstract: A serological follow-up study of 3.5 years duration was done of a dairy herd that had experienced a mass seroconversion to Neospora caninum following a point source exposure shortly before the 17th of January 2000. A total of 913 blood samples of 244 animals at seven sampling dates were used to investigate the seroprevalence dynamics in the herd.Most postnatally infected cattle remained seropositive during the period of investigation but 11 animals became seronegative after 6-27 months indicating transient inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
2
11
0
1
Order By: Relevance
“…Fluctuations in the results similar to these have previously been described (McINNES et al, 2006;DIJKSTRA et al, 2008;MORÉ et al, 2009;YAO et al, 2009;MARQUES et al, 2011). McInnes et al (2006) reported that there was no correlation between the serological tests on dams and the PCR on their fetuses, and a high percentage of infected fetuses had serologically negative dams.…”
Section: Discussionsupporting
confidence: 72%
“…Fluctuations in the results similar to these have previously been described (McINNES et al, 2006;DIJKSTRA et al, 2008;MORÉ et al, 2009;YAO et al, 2009;MARQUES et al, 2011). McInnes et al (2006) reported that there was no correlation between the serological tests on dams and the PCR on their fetuses, and a high percentage of infected fetuses had serologically negative dams.…”
Section: Discussionsupporting
confidence: 72%
“…Several factors can affect the PCR techniques; sensitivity, specificity, parasite detectability in the presence of host DNA and defective templates, mainly linked to quality of DNA extraction, additionally a false positive result due to contamination at nested-PCR is reported (MÜLLER et al, 2001;MARQUES et al, 2011). Fluctuating of N. caninum antibody levels in naturally infected cows was previously described (CARDOSO et al, 2012;CONRAD et al, 1993;DIJKSTRA et al, 2008;KYAW et al, 2005;MARQUES et al, 2011). The observation that some infected dams can exhibit negative antibody values during any gestational period, particularly Neospora at parturition or abortion was previously demonstrated (BENAVIDES et al, 2012;NOGAREDA et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…40 Also, transplacental infection may be more likely to occur in dams that were themselves prenatally infected compared with postnatally infected dams. 41 The risk of abortion was positively correlated with N. caninum-specific antibodies in individual animals 42 and severity of fetal Neosporaassociated lesions also increased with higher maternal seropositivity. 43 Cows with high antibody titers (≥400) showed higher vertical transmission frequency (94.8%) than cows with low antibody titers of 25-200 (14.8%).…”
Section: Transmissionmentioning
confidence: 93%